Model Klasik Manajemen Pendidikan Islam Dan Relevansinya Kini - Muhamad Geri Gunawan; Mulyawan Safwandy Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study discusses the classical model of Islamic education management (MPI) and its relevance in responding to contemporary educational challenges. The background of this study stems from the issue of the dichotomy of knowledge, the crisis of morality, and the tendency of modern education to be pragmatic and emphasise only cognitive achievements. The method used is literature research with data sources in the form of classical books, including Ta'lim al-Muta'allim by Al-Zarnuji and Adabul 'Alim wal Muta'allim by KH. Hasyim Asy'ari, the thoughts of figures such as Ibn Khaldun and Ibn Miskawaih, as well as 31 academic documents in the form of Sinta/Scopus indexed articles and supporting books. The analysis was conducted descriptively-analytically and comparatively, with validity maintained through literature triangulation. The results of the study show that the classical MPI model is based on the values of tauhid, adab, akhlak, ukhuwah, and amanah. These values are embodied in the kuttab, madrasah, halaqah systems, as well as teacher-student relationships based on exemplary behaviour. This model forms a holistic and integrative educational framework, uniting spiritual, moral, and intellectual aspects. Theoretically, this study enriches the value-based MPI knowledge base. Practically, it provides direction for the management of educational institutions to remain rooted in spirituality while being adaptive to developments. Prospectively, the classical MPI model is relevant for strengthening moral education in the digital age.